2017
DOI: 10.3389/fphys.2017.00479
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Non-responders for Glucose Control Markers after 10 Weeks of High-Intensity Interval Training in Adult Women with Higher and Lower Insulin Resistance

Abstract: Background: Exercise training improves performance and biochemical parameters on average, but wide interindividual variability exists, with individuals classified as responders (R) or non-responders (NRs), especially between populations with higher or lower levels of insulin resistance. This study assessed the effects of high-intensity interval training (HIIT) and the prevalence of NRs in adult women with higher and lower levels of insulin resistance.Methods: Forty adult women were assigned to a HIIT program, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 45 publications
2
37
1
2
Order By: Relevance
“…Aunque factores genéticos 13 , y ambientales [14][15][16] han sido escuetamente explorados, aún no se identifican los potenciales factores ambientales que dan cuenta de este fenómeno. Descartando la influencia genética que varía individualmente, no está del todo claro qué parámetros de salud, por ejemplo, composición corporal, presión arterial o marcadores metabólicos como los triglicéridos, presentan mayor o menor prevalencia de sujetos no respondedores en la población adherente a ejercicio.…”
unclassified
“…Aunque factores genéticos 13 , y ambientales [14][15][16] han sido escuetamente explorados, aún no se identifican los potenciales factores ambientales que dan cuenta de este fenómeno. Descartando la influencia genética que varía individualmente, no está del todo claro qué parámetros de salud, por ejemplo, composición corporal, presión arterial o marcadores metabólicos como los triglicéridos, presentan mayor o menor prevalencia de sujetos no respondedores en la población adherente a ejercicio.…”
unclassified
“…The current study demonstrated how recently proposed statistical approaches (Hopkins 2000b;Swinton et al 2018) can be used to improve the confidence when classifying non-responders. The major novel findings are: 1) despite its growing popularity in the individual response literature (Scharhag-Rosenberger et al 2012;Astorino and Schubert 2014;Ross et al 2015;Gurd et al 2016;Alvarez et al 2017;de Lannoy et al 2017;Montero and Lundby 2017;Astorino TA et al 2018), threshold-based dichotomous classification approaches misclassify individuals who have a high probability of a positive response as non-responders, and 2) using response CIs with zeroand/or SWC-based thresholds provides more information than dichotomous classification approaches regarding an individual's response. Application of these statistical approaches has the potential to improve evidenceinformed exercise prescription decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the recent literature has dichotomously classified individuals as either "responders" or "non-responders" using a pre-determined threshold (Scharhag-Rosenberger et al 2012;Astorino and Schubert 2014;Ross et al 2015;Montero and Lundby 2017) including two times the typical error (2x TE) (Bouchard et al 2012;Bonafiglia et al 2016;Gurd et al 2016;Raleigh et al 2016;Alvarez et al 2017;de Lannoy et al 2017;Astorino TA et al 2018). Although 2x TE is a relatively robust threshold for the classification of "responders" (i.e., the true change for observed responses >29 TE above zero is >90% likely to be positive) (Hopkins 2000a), dichotomous classification of "non-responders" has significant limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, some individuals show improvements with exercise training (eg, decrease in fasting glucose) and are considered responders , whereas others may not have such a response (eg, no change or even increases in fasting glucose) and are considered non‐responders . Individual variability has been reported mainly regarding fitness‐related variables, and in response to moderate‐intensity endurance (ET), resistance (RT), or high‐intensity interval training (HIT), and also in different age groups such as children, adults, or older populations, The existence of non‐responders for glucose homeostasis‐related variables has been confirmed more recently . In the present study, we confirmed a wide interindividual variability that is independent of the training‐induced changes after HIT, RT, or CT with regard to 20 outcomes and risk parameters, including 9 body composition, 3 cardiovascular, 3 metabolic, and 5 performance parameters.…”
Section: Perspectivesmentioning
confidence: 99%